PERAN SISTEM PENGENDALIAN INTERNAL DALAM MENEKAN ANGKA KREDIT MACET (Studi Kasus pada PT. FIFGROUP Kantor Cabang Jember) - Ningrum Suryadinata; Akhmad Toha; Aryo Prakoso (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
This study aims to explain and describe the role of internal control system of PT. FIFGROUP Branch Office in Jember for pressing the number of bad loans. This research is a descriptive research with qualitative approach. Types of data used are quantitative and qualitative data. Quantitative data is a company credit report. Qualitative data in the form of data relating to the state of the company in the form of and supporting factors in the environment that is not in the form of figures in the form of general overview of the company and types of products sold, data collected by observation, interview, documentation, and triangulation, then analyzed by data reduction, display data, and conclusion drawing / verification and describe credit report and interview result. The results showed that the role of internal control system as the controlling of credit management performance applied by PT. FIFGROUP Jember Branch Office is still less than optimal in suppressing the number of bad loans. The first is the element of the control environment, which is contained in the management indicators are more concerned with the environmental factors of the office. Factors that cause bad loans in this element exist in two factors, the first is the internal factors and external factors. Both factors are causing an increase in the trend of problematic accounts receivable on DANASTRA, SPEKTRA and FIFASTRA products in 2016 and 2017. Other deficiencies, there is in the element of control activities that is less optimal in checking the data history of prospective borrowers and checking process on debtors DANASTRA on business development